ANALISIS ASUHAN KEPERAWATAN NYERI AKUT PADA PASIEN NY. W POST SECTIO CAESAREA DENGAN RELAKSASI GENGGAM JARI DI RUANG GAYATRI RST WIJAYAKUSUMA PURWOKERTO - Danar Puspitowati; Eka Widiastuti; Faiq Aji Kurniawan; Tin Utami (Bajang Institute, 2022)
Sectio caesarea (SC) is a delivery that requires surgery. Post-SC patients will experience physical or physiological impacts, namely pain, this incident occurs after SC because it is caused by tissue nicks during surgery. Common complementary therapies for patients with pain problems are meditation, autogenic exercises, relaxation exercises, guided imagination, rhythmic breathing, operant conditioning, biofeedback, establishing a therapeutic relationship, therapeutic touch, skin stimulation, hypnosis, music, acupressure, and aromatherapy. Finger grip relaxation is a relaxation technique that is very simple and easy to do Methods: Descriptive research design in the form of a case study with a nursing process approach consisting of assessment, nursing diagnosis, planning, implementation, and evaluation by focusing on nursing implementation in post SC patients with pain acutely by providing finger grip relaxation. The subject of the case study amounted to one case, namely a post SC patient with acute pain at Wijayakusuma RST Purwokerto. Results: The results showed that the problems that occurred in the client could be resolved on the 3rd day and were characterized by normal breathing frequency (20 x/minute), BP 110/70 mmHg; N 80 x/minute, the patient looks more relaxed and the pain scale becomes 3. Conclusion: The finger grip relaxation nursing action performed on the patient showed an increase in the patient's sense of comfort, thereby reducing the patient's pain.